Alteration of 29Si-doped SON68 borosilicate nuclear waste glass in the presence of near field materials. (December 2019) - Bouakkaz, Rachid; Abdelouas, Abdesselam; El Mendili, Yassine; David, Karine; Grambow, Bernd
Abstract: The leaching of 29 Si-doped SON68 French nuclear waste glass was investigated in Callovo-Oxfordian (COx) water in the presence of P235GH stainless steel and COx argillite. Experiments were carried out to understand the effect of near-field materials on the rate of glass dissolution and the migration of 29 Si in the claystone core. Tests were performed by using percolation cells containing glass and stainless steel sandwiched between two clay cores in two different combinations: glass/clay at 50 and 90 °C, and glass/steel/clay/at 90 °C. COx water was injected through the percolation cells at 120 bars (solution flow rate 0.05–0.38 mL d −1 ). Results showed that the presence of steel did not enhance the dissolution rate of the glass despite the retention of 29 Si released from the glass on the corrosion products. The glass dissolution rate up to 17 months tends towards 10 −4 and 10 −3 g m −2 d −1 at 50 and 90 °C, respectively. The glass alteration in the presence of clay leads to the formation of calcite and Mg-silicates at 50 °C in addition to apatite and powellite at 90 °C. The main steel corrosion products were siderite, magnetite, ferrosilicates, pyrite, pyrrhotite, troilite and mackinawite. MgSO4 and CaSO4 were also identified in the presence of steel. Highlights: Glass alteration under disposal conditions. Iron and clay do not affect glass corrosion kinetics. Long term alteration of the glass is low.